(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
The rectangular opening which is 20% of the apex wall area works as a gate within a two-cycle sharp-crested labyrinth weir, reduces the effects of immersion upstream, and allows passing sediments. In the result of experimental investigation, the discharge capacity of the labyrinth combined flow related to geometric dimensions; that is where the increase in the sidewall and the apex lengths reduce the immersion, while the discharge increases (23-32%) and when the weir crest level increases about (30%). The combined discharge coefficient decreases when increasing the ratio value of the head to the weir height, its value also decreases by (6-21%) when increasing the sidewall length 3 times. The proposed equation for predicting the combined discharge is within (0.07-0.16%) of the measured discharge. The contribution analysis of each discharge part of this structure indicates the gate passes (40-60%) less than discharged from the weir due to the submergence; Moreover, this state causes head lifting on the weir crest by (26%) and this increases is reflected as an advantage to the weir in its discharging.